2005
DOI: 10.3844/ajbbsp.2005.90.94
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-density Lipoprotein Upregulates GM2 Activator Protein Gene Expression

Abstract: Oxidized low-density lipoprotein (LDL) has been shown to be a powerful regulator of gene expression in monocyte-derived macrophage. To determine the effects of oxidized LDL on macrophage gene expression, macrophages incubated with native or oxidized LDL were analyzed by differential display technique. The differentially expressed cDNA (387 bp) fragment by oxidized LDL showed 100% homology to the part of 3’-untranslated region of the gene of human GM2 activator protein. Quantitative RT-PCR data using specific T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…METH toxicity is frequently reported as a potential model of drug induced Parkinsonism, which is one of the most common movement disorders of the elderly. Chronic or intermittent METH abuse may create temporary or permanent disturbances in the dopaminergic systems of the brain that may predispose individuals to Parkinsonism (Kita et al, 2003;Fisher et al, 2005;Yanai et al, 2005;Tolwani et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…METH toxicity is frequently reported as a potential model of drug induced Parkinsonism, which is one of the most common movement disorders of the elderly. Chronic or intermittent METH abuse may create temporary or permanent disturbances in the dopaminergic systems of the brain that may predispose individuals to Parkinsonism (Kita et al, 2003;Fisher et al, 2005;Yanai et al, 2005;Tolwani et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Up‐regulated Cer and GM2 were strongly associated with AS (Gouni‐Berthold et al, 2001; Panagiotis et al, 2015; Yu et al, 2015). It is reported that GM2 ganglioside activator protein is a general lipid transporter in macrophages, which is regulated by ox‐LDL and subsequently enhances glycosphingolipid accumulation (Yanai, 2005; Yanai et al, 2006). Cer, as the second messengers of cells and the metabolic hub of sphingolipid, produced a variety of biological effects in the cardiovascular system: inducing apoptosis of smooth muscle and myocardial cells, regulating immune function and inflammatory response, participating in oxidative stress, etc.…”
Section: Discussionmentioning
confidence: 99%